Investigation of long period oscillations in an enclosed harbor. - Cruz, Eric C.; Aono, T.
Field measurements were conducted to verify and quantify the long period oscillations in Hiratsuka Harbor in Japan. Time series data of water surface displacements were synthesized and wave statistics of the surf beat component obtained. A nonlinear dispersive wave model was used to simulate the wave transformation around and within the harbor, using part of measured time series for the incident wave. The measured time series, frequency spectra and significant wave statistics of the long period components at the gauging stations were adequately simulated in the computation. Applications to the simulation of the wave field due to a critical wave for two harbor design scenarios are shown.
Keywords: Oscillations; Nonlinear dispersive wave model